Conceptualization of religion in Linguistic Consciousness of Kazakh Ethnicity - Kuzembayeva, G.A.; Shonmurinov , T.Е. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
Religion is the only area where rational-analytical activity, which is obligatory for science, provokes a tense attitude towards itself. In this respect, the identification of religion as a concept, describing its content, structure, and development, as well as its impact on the nation causes a high interest. The article presents the results of a psycholinguistic study, the purpose of which was to describe the ways of conceptualizing religion by the representatives of the Kazakh language and culture, modeling the associative field “religion” in the Kazakh language, identifying the features of conceptualizing religion in the Kazakh linguistic culture. The material of the research was the data of psycholinguistic study conducted with the native speakers of the Kazakh language. The method of obtaining data was a free associative experiment with the registration of answers given for a certain period of time to the stimulus word дін / religion. The obtained associative data were distributed according to the frequency criterion, followed by modeling the associative field and its cognitive structure. The associative field “religion” in the Kazakh linguistic consciousness includes agents and artifacts of religion, rituals, beliefs, immaterial aspects, figures, and types of religion. The most frequent associations with religion in the Kazakh linguistic consciousness are мешіт / mosque (13%), Құдай / God (11%), сенім / faith (10%), Ислам / Islam (10%), шіркеу / church (9.5%), Құран / Quran (7.5%), жан / soul (7%), жарық / light (6%), атеизм / atheism (5.5%), дұға ету / pray (5%). The associative field “religion / дін” modelled as a result of the psycholinguistic study consists of the features ‘Islam’, ‘mosque’, ‘God’, and ‘faith’ in the centre of the field, and the features ‘bata’, ‘pray, ‘zeket’, and ‘oraza’ in the near periphery of the field model “religion / дін”, which demonstrates the relevance of these Islamic religious artifacts and acts to the Kazakh linguistic consciousness.